Analisis Pengaruh Sanksi Pajak, Pelayanan Fiskus,Pengetahuan Dan Kesadaranterhadap Kepatuhanwajib Pajak Di Samsat Medan Selatan - Siregar, Indria Sari; Lubis, Yusniar; Hartono, Budi (Mahesa Research Center, 2023)
This study aims to determine and analyze the effect of Tax Sanctions, Fiscal Services, Knowledge, and Awareness on Taxpayer Compliance in the South Medan Samsat. This type of research is quantitative research. The sample in this study was all Medan City Communities (taxpayers) and taxpayers who owned vehicles registered at the South Medan SAMSAT totaling 105 people. And the data analysis technique uses the SPSS (Statiskal Package for the Social Sciences) technique which is an application program that has the ability for quite high statistical analysis and a data management system in a graphical environment. The results in this study indicate that Tax Sanctions, Fiskus Services and Awareness have a positive and significant influence on Taxpayer Compliance at the South Medan SAMSAT. While on the other hand it is proven that knowledge has a positive but not significant effect on taxpayer compliance at the South Medan Samsat.